Semiconductor nanoparticles and method for manufacturing the same, and light-emitting device

CN115717065BActive Publication Date: 2025-03-07NAT UNIV CORP TOKAI NAT HIGHER EDUCATION & RES SYST +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211303175.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-02-15
Filing Date
2018-02-28
Publication Date
2025-03-07
Estimated Expiration
2038-02-28

AI Technical Summary

Technical Problem

The existing semiconductor nanoparticles have a peak luminescence wavelength in longer wavelength regions, making it difficult to achieve short-wavelength band edge luminescence.

Method used

A semiconductor nanoparticles composed of Ag, In, Ga and S have a ratio of the number of Ga atoms to the total number of In and Ga. The ratio of light irradiation is 0.95 or less, and the light irradiation peak wavelength is made in the range of 500 nm or more and less than 590 nm, and the nanoparticles are manufactured by heat treatment.

Benefits of technology

实现了半导体纳米粒子的频带边缘发光,并具有短波长的发光峰值波长,提升了光谱的窄带性和发光效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115717065B_ABST
    Figure CN115717065B_ABST
Patent Text Reader

Abstract

The present invention provides a semiconductor nanoparticle, which exhibits band edge luminescence and has a short wavelength luminescence peak wavelength. The semiconductor nanoparticle contains Ag, In, Ga and S, and the ratio of the number of atoms of Ga to the total number of atoms of In and Ga is 0.95 or less. In addition, the semiconductor nanoparticle emits light having a luminescence peak wavelength in the range of 500 nm to less than 590 nm, and the half-value width of the luminescence peak is 70 nm or less, and the average particle size is 10 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of application number: 201880014289.9, application date: 2018.2.28, invention name: "Semiconductor nanoparticles and their manufacturing method, and light-emitting device" (PCT / JP2018 / 007580). Technical Field

[0002] The invention relates to semiconductor nanoparticles and a manufacturing method thereof, and a light-emitting device. Background Art

[0003] It is known that semiconductor particles will show quantum size effect when their particle size is, for example, less than 10nm, and such nanoparticles are called quantum dots (also called semiconductor quantum dots). The quantum size effect refers to the phenomenon that the energy bands of the valence band and conduction band, which are considered to be continuous in the main particle, are discrete in the nanoparticle, and the band gap energy changes according to the particle size.

[0004] Quantum dots can absorb light and convert the wavelength into light corresponding to the band gap energy, so white light emitting devices using the light emitted by quantum dots are proposed (for example, refer to Japanese Patent Publication No. 2012-212862 and Japanese Patent Publication No. 2010-177656). Specifically, it is proposed to make quantum dots absorb part of the light emitted from the light emitting diode (LED) chip and obtain white light in the form of a mixed color of the light emitted from the quantum dots and the light emitted from the LED chip. In these patent documents, it is proposed to use binary quantum dots of the 12th-16th group such as CdSe and CdTe, and the 14th-16th group such as PbS and PbSe. In addition, as semiconductor nanoparticles that can emit band edge light and can be a ternary system with low toxicity composition, tellurium compound nanoparticles (for example, refer to Japanese Patent Publication No. 2017-014476) and sulfide nanoparticles (for example, refer to Japanese Patent Publication No. 2017-025201). Summary of the invention

[0005] Problems to be solved by the invention

[0006] However, the semiconductor nanoparticles described in Japanese Patent Application Publication No. 2017-014476 and Japanese Patent Application Publication No. 2017-025201 have a luminescence peak wavelength in a relatively long wavelength region. Therefore, an object of one embodiment of the present invention is to provide a semiconductor nanoparticle that exhibits band edge luminescence and has a luminescence peak wavelength of a short wavelength.

[0007] Means for solving problems

[0008] The first option is a semiconductor nanoparticle, which contains Ag, In, Ga and S, wherein the ratio of the number of Ga atoms to the total number of In and Ga atoms is less than 0.95, and the semiconductor nanoparticle emits light having a luminescence peak wavelength in the range of greater than 500nm and less than 590nm and a half-value width of the luminescence peak of less than 70nm when irradiated with light, and the average particle size is less than 10nm.

[0009] The second embodiment is a method for producing semiconductor nanoparticles, which includes: preparing a mixture containing silver acetate, indium acetylacetonate, gallium acetylacetonate, a sulfur source and an organic solvent; and heat-treating the mixture.

[0010] A third embodiment is a light-emitting device comprising: a light-converting member including the semiconductor nanoparticles described above; and a semiconductor light-emitting element.

[0011] Effects of the Invention

[0012] According to one aspect of the present invention, there can be provided a semiconductor nanoparticle which exhibits band-edge luminescence and has a short-wavelength luminescence peak wavelength. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a diagram showing the light emission spectrum of semiconductor nanoparticles.

[0014] Figure 2 This is a diagram showing the absorption spectrum of semiconductor nanoparticles.

[0015] Figure 3 This is the XRD spectrum of the semiconductor nanoparticles involved in Example 4.

[0016] Figure 4 It is a diagram showing the light emission spectrum of semiconductor nanoparticles.

[0017] Figure 5 This is a diagram showing the absorption spectrum of semiconductor nanoparticles.

[0018] Figure 6 It is a graph showing the emission spectra of the core-shell type semiconductor nanoparticles according to Examples 12 to 16.

[0019] Figure 7 This is a graph showing the emission spectra of the core-shell type semiconductor nanoparticles according to Examples 17 and 18.

[0020] Figure 8 This is a graph showing the emission spectrum of the TOP-modified core-shell type semiconductor nanoparticles of Example 19. DETAILED DESCRIPTION

[0021] Hereinafter, the embodiments are described in detail. However, the embodiments shown below are embodiments for illustrating semiconductor nanoparticles and methods for making the same and light-emitting devices for concretizing the technical idea of ​​the present invention, and the present invention is not limited to the semiconductor nanoparticles and methods for making the same and light-emitting devices shown below. In addition, in this specification, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes, as long as the intended purpose of the process can be achieved. When there are multiple substances belonging to each component in the composition, the content of each component in the composition refers to the total amount of the multiple substances present in the composition unless otherwise specified.

[0022] Semiconductor Nanoparticles

[0023] The semiconductor nanoparticles of the first embodiment include silver (Ag), indium (In), gallium (Ga) and sulfur (S). The ratio of the number of atoms of Ga in the semiconductor nanoparticles to the total number of atoms of In and Ga (Ga / (Ga+In)) is 0.95 or less. The semiconductor nanoparticles emit light with a luminescence peak wavelength in the range of more than 500nm and less than 590nm by light irradiation, and the half-value width of the luminescence peak in the luminescence spectrum is less than 70nm. In addition, the average particle size of the semiconductor nanoparticles is less than 10nm.

[0024] The semiconductor nanoparticles contain Ag, In, Ga and S, and the ratio of the number of Ga atoms to the total number of In and Ga atoms is within a specified range, thereby having a longer wavelength than the excitation light, having a luminescence peak wavelength in the range of more than 500nm and less than 590nm which is the visible region, and being able to emit band-edge light.

[0025] The crystal structure of semiconductor nanoparticles can be set to at least one selected from tetragonal, hexagonal and orthorhombic. Generally speaking, in the literature, the semiconductor nanoparticles shown in the composition formula of AgInS2 are introduced as semiconductor nanoparticles containing Ag, In and S and having a crystal structure of tetragonal, hexagonal or orthorhombic. The semiconductor nanoparticles involved in the present embodiment can also be considered as semiconductor nanoparticles after, for example, a part of In as a 13th group element is replaced with Ga which is also a 13th group element. That is, the composition of semiconductor nanoparticles is represented by Ag-In-Ga-S or Ag(In, Ga)S2, for example.

[0026] It is explained that the semiconductor nanoparticles shown in the composition formula such as Ag-In-Ga-S and having a hexagonal crystal structure are wurtzite-type semiconductors, and the semiconductor nanoparticles shown in the composition formula such as Ag-In-Ga-S and having a tetragonal crystal structure are chalcopyrite-type semiconductors. The crystal structure is identified, for example, by measuring the XRD spectrum obtained by X-ray diffraction (XRD) analysis. Specifically, the XRD spectrum obtained by the semiconductor nanoparticles is compared with the XRD spectrum of the semiconductor nanoparticles shown as the composition of AgInS2 or the XRD spectrum obtained by simulating the crystal structure parameters. In the known spectrum and the simulated spectrum, as long as there is a spectrum consistent with the spectrum of the semiconductor nanoparticles, the crystal structure of the semiconductor nanoparticles can be said to be the crystal structure of the known or simulated spectrum that is consistent with it.

[0027] In the aggregate of semiconductor nanoparticles, semiconductor nanoparticles having different crystal structures may be mixed. In this case, peaks derived from a plurality of crystal structures are observed in the XRD spectrum.

[0028] The semiconductor nanoparticles may be substantially composed of only Ag, In, Ga, and S. Here, the term "substantially" is used in consideration of the fact that other elements other than Ag, In, Ga, and S are inevitably contained due to mixing of impurities or the like.

[0029] The ratio of the number of Ga atoms to the total number of In and Ga atoms, Ga / (Ga+In) (hereinafter also referred to as “Ga ratio”) may be 0.95 or less, and more preferably 0.2 or more and 0.9 or less.

[0030] The ratio of the number of Ag atoms to the total number of Ag, In, and Ga atoms, Ag / (Ag+In+Ga) (hereinafter also referred to as “Ag ​​ratio”) may be 0.05 or more and 0.55 or less.

[0031] The Ag ratio may be 0.3 to 0.55, and the Ga ratio may be 0.5 to 0.9, and preferably the Ag ratio may be 0.35 to 0.53, and the Ga ratio may be 0.52 to 0.86.

[0032] The Ga ratio can be greater than 0.2 and less than 0.9, and the value of Ga ratio + 2×Ag ratio can be greater than 1.2 and less than 1.7. Preferably, the Ga ratio can be greater than 0.2 and less than 0.9, the Ag ratio can be greater than 0.3 and less than 0.55, and the value of Ga ratio + 2×Ag ratio can be greater than 1.2 and less than 1.7.

[0033] The Ag ratio may be 0.05 to 0.27, and the Ga ratio may be 0.25 to 0.75. Preferably, the Ag ratio may be 0.06 to 0.27, and the Ga ratio may be 0.26 to 0.73.

[0034] The Ga ratio can be greater than 0.2 and less than 0.8, and the value of Ga ratio + 2×Ag ratio can be greater than 0.6 and less than 1. Preferably, the Ga ratio can be greater than 0.2 and less than 0.8, the Ag ratio can be greater than 0.05 and less than 0.4, and the value of Ga ratio + 2×Ag ratio can be greater than 0.6 and less than 1.

[0035] The ratio S / (Ag+In+Ga) of the number of S atoms to the total number of Ag, In, and Ga atoms (hereinafter also referred to as “S ratio”) may be, for example, 0.6 or more and 1.6 or less.

[0036] The chemical composition of semiconductor nanoparticles can be identified, for example, by X-ray fluorescence analysis (XRF). The Ga ratio calculated as Ga / (Ga+In), the Ag ratio calculated as Ag / (Ag+In+Ga), and the S ratio calculated as S / (Ag+In+Ga) are calculated based on the chemical composition measured by this method.

[0037] The semiconductor nanoparticles have an average particle size of less than 10 nm. The average particle size can be, for example, less than 10 nm, preferably less than 5 nm. If the average particle size exceeds 10 nm, it is difficult to obtain the quantum size effect, and it is difficult to obtain the band edge luminescence. In addition, the lower limit of the average particle size is, for example, 1 nm.

[0038] The particle size of semiconductor nanoparticles can be obtained, for example, by using a TEM image taken using a transmission electron microscope (TEM). Specifically, the length of the longest line segment obtained by connecting any two points of the particle periphery observed with a TEM image of a certain particle and passing through the inside of the particle is set as the particle size of the particle.

[0039] However, in the case where the particle is a particle with a rod shape, the length of the minor axis is regarded as a particle diameter. Here, the rod-shaped particle refers to: a particle having a minor axis and a major axis orthogonal to the minor axis in the TEM image, and the ratio of the length of the major axis to the length of the minor axis is greater than 1.2. In the TEM image, the rod-shaped particle is observed in the form of a rectangular quadrangular shape, an elliptical shape or a polygonal shape, for example. The shape of the cross section of the face orthogonal to the major axis as a rod shape can be, for example, a circle, an ellipse or a polygon. Specifically, for the rod-shaped particle, when the cross section is an elliptical shape, the length of the major axis refers to the length of the longest line segment in the line segment connecting any two points of the particle periphery, and when the cross section is a rectangular shape or a polygonal shape, the length of the major axis refers to the length of the longest line segment in the line segment parallel to the longest side in the side of the prescribed periphery and connecting any two points of the particle periphery. The length of the minor axis refers to the length of the line segment orthogonal to the line segment of the length of the above-mentioned major axis in the line segment connecting any two points of the periphery, and the length of the longest line segment.

[0040] Regarding the average particle size of semiconductor nanoparticles, the particle size is measured for all measurable particles observed in TEM images at 50,000 times or more and 150,000 times or less, and is set as the arithmetic average of these particle sizes. Here, "measurable" particles are particles in which the entire particle can be observed in the TEM image. Therefore, in the TEM image, a part of it is not included in the shooting range and is "cut off" as if it is not a measurable particle. When the number of measurable particles contained in one TEM image is more than 100, the TEM image is used to obtain the average particle size. On the other hand, when the number of measurable particles contained in one TEM image is less than 100, the shooting location is changed, and the TEM image is obtained again. The particle size of more than 100 measurable particles contained in two or more TEM images is measured to obtain the average particle size.

[0041] Semiconductor nanoparticles include Ag, In, Ga and S, and the atomic number of Ga is a specified range relative to the ratio of the total atomic number of In and Ga, so that band edge luminescence can be performed. Semiconductor nanoparticles are irradiated with light having a peak near 365nm, thereby having a luminescence peak wavelength in the range of more than 500nm and less than 590nm and luminescing. The luminescence peak wavelength can be, for example, more than 500nm and less than 580nm, more than 500nm and less than 575nm, more than 505nm and less than 575. In addition, it can also be more than 570nm and less than 585nm or more than 575nm and less than 580nm. The half-value width of the luminescence peak in the luminescence spectrum can be, for example, less than 70nm, less than 60nm, less than 55nm or less than 50nm. The lower limit of the half-value width can be, for example, more than 10nm or more than 20nm.

[0042] The semiconductor nanoparticles may be semiconductor nanoparticles that impart other luminescence, such as defect luminescence, while imparting band edge luminescence. Defect luminescence generally has a long luminescence lifetime and a broad spectrum, with its peak on the longer wavelength side than the band edge luminescence. In the case of obtaining both band edge luminescence and defect luminescence, it is preferred that the intensity of the band edge luminescence is greater than the intensity of the defect luminescence.

[0043] The band edge luminescence of semiconductor nanoparticles can change its peak position by changing the shape and / or average particle size, especially the average particle size, of the semiconductor nanoparticles. For example, if the average particle size of the semiconductor nanoparticles is further reduced, the band gap energy becomes larger due to the quantum size effect, and the peak wavelength of the band edge luminescence can be shifted to the short wavelength side.

[0044] In addition, the peak position of the band edge emission of semiconductor nanoparticles can be changed by changing the composition of the semiconductor nanoparticles. For example, by increasing the Ga ratio, the peak wavelength of the band edge emission can be shifted to the shorter wavelength side.

[0045] Semiconductor nanoparticles are preferably semiconductor nanoparticles whose absorption spectrum shows exciton peaks. Exciton peaks are peaks obtained because of generating excitons, and they are embodied in the absorption spectrum and refer to particles that are suitable for band edge luminescence that the distribution of particle diameter is small and crystal defects are few. The more abrupt the exciton peak is, the more particles that the aggregate of semiconductor nanoparticles contains more consistent particle diameters and few crystal defects, so the half-value width of the predicted luminescence narrows and the luminous efficiency improves. In the absorption spectrum of the semiconductor nanoparticles of the present embodiment, for example, more than 450nm and less than 590nm, observe the exciton peak.

[0046] The surface of the semiconductor nanoparticles may be modified with a surface modifier. The surface modifier is, for example, a surface modifier for stabilizing the semiconductor nanoparticles to prevent aggregation or growth of the particles and / or a surface modifier for improving the dispersibility of the particles in a solvent.

[0047] As the surface modifier, for example, nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, oxygen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, etc. can be cited. As the hydrocarbon group with 4 to 20 carbon atoms, saturated aliphatic hydrocarbon groups such as n-butyl, isobutyl, n-pentyl, n-hexyl, octyl, decyl, dodecyl, hexadecyl, octadecyl, etc. can be cited; unsaturated aliphatic hydrocarbon groups such as oleyl; alicyclic hydrocarbon groups such as cyclopentyl and cyclohexyl; aromatic hydrocarbon groups such as phenyl, benzyl, naphthyl, naphthylmethyl, etc., among which saturated aliphatic hydrocarbon groups or unsaturated aliphatic hydrocarbon groups are preferred. As the nitrogen-containing compound, amines and amides can be cited, as the sulfur-containing compound, thiols can be cited, and as the oxygen-containing compound, fatty acids can be cited.

[0048] As the surface modifier, a nitrogen-containing compound having a hydrocarbon group having 4 to 20 carbon atoms is preferred. Examples of such nitrogen-containing compounds include alkylamines such as n-butylamine, isobutylamine, n-pentylamine, n-hexylamine, octylamine, decylamine, dodecylamine, hexadecylamine, and octadecylamine; and alkenylamines such as oleylamine.

[0049] As the surface modifier, a sulfur-containing compound having a hydrocarbon group having 4 to 20 carbon atoms is also preferred. Examples of such sulfur-containing compounds include alkyl mercaptans such as n-butyl mercaptan, isobutyl mercaptan, n-pentyl mercaptan, n-hexyl mercaptan, octyl mercaptan, decanethiol, dodecanethiol, hexadecanethiol, and octadecyl mercaptan.

[0050] The surface modifier may be a combination of two or more different surface modifiers, for example, a combination of one compound selected from the nitrogen-containing compounds exemplified above (such as oleylamine) and one compound selected from the sulfur-containing compounds exemplified above (such as dodecanethiol).

[0051] Method for producing semiconductor nanoparticles

[0052] The method for producing semiconductor nanoparticles according to the second embodiment includes: preparing a mixture containing a silver salt, an indium salt, a gallium salt, a sulfur source, and an organic solvent; and heat treating the prepared mixture. Preferably, the mixture includes silver acetate, indium acetylacetonate, gallium acetylacetonate, sulfur or thiourea as a sulfur source, and an organic solvent.

[0053] The mixture can be prepared by adding a silver salt, an indium salt, a gallium salt and a sulfur source to an organic solvent and mixing. The content ratio of Ag, In, Ga and S in the mixture is appropriately selected according to the target composition. For example, the molar ratio of Ga relative to the total molar amount of In and Ga is 0.2 or more and 0.9 or less. In addition, for example, the molar ratio of Ag relative to the total molar amount of Ag, In and Ga is 0.05 or more and 0.55 or less. In addition, for example, the molar ratio of S relative to the total molar amount of Ag, In and Ga is 0.6 or more and 1.6 or less.

[0054] As organic solvents, there are: amines having a hydrocarbon group with a carbon number of 4 or more and 20 or less, especially alkylamines or alkenylamines having a carbon number of 4 or more and 20 or less; thiols having a hydrocarbon group with a carbon number of 4 or more and 20 or less, especially alkylthiols or alkenylthiols having a carbon number of 4 or more and 20 or less; phosphines having a hydrocarbon group with a carbon number of 4 or more and 20 or less, especially alkylphosphines or alkenylphosphines having a carbon number of 4 or more and 20 or less. These organic solvents can eventually become substances for surface modification of the obtained semiconductor nanoparticles. These organic solvents can be used in combination of two or more, and in particular, a mixed solvent composed of at least one selected from thiols having a hydrocarbon group with a carbon number of 4 or more and 20 or less and at least one selected from amines having a hydrocarbon group with a carbon number of 4 or more and 20 or less can be used. These organic solvents can also be used in combination with other organic solvents.

[0055] In the method for producing semiconductor nanoparticles, semiconductor nanoparticles are generated in an organic solvent by heat treating the mixture. The temperature of the heat treatment of the mixture is, for example, 230°C or more and 310°C or less, preferably higher than 260°C and 310°C or less, more preferably 290°C or more and 310°C or less. The time of the heat treatment is, for example, 5 minutes or more and 20 minutes or less, preferably 5 minutes or more and 15 minutes or less. The heat treatment of the mixture can be carried out at more than 2 temperatures. For example, it can be heated at a temperature of 30°C or more and 155°C or less for more than 1 minute and less than 15 minutes, and then heated at a temperature of 230°C or more and 310°C or less for more than 5 minutes and less than 20 minutes.

[0056] The atmosphere for the heat treatment is preferably an inert atmosphere, particularly an argon atmosphere or a nitrogen atmosphere. By using an inert atmosphere, the by-production of oxides and the oxidation of the surface of semiconductor nanoparticles can be reduced or prevented.

[0057] After the generation of semiconductor nanoparticles is completed, the obtained semiconductor nanoparticles can be separated from the treated organic solvent, or further purified as needed. Separation can be performed, for example, by centrifuging the organic solvent containing the nanoparticles after the generation is completed, and taking out the supernatant containing the nanoparticles. Purification can be performed, for example, by adding an organic solvent to the supernatant and then centrifuging it, and taking out the semiconductor nanoparticles in the form of a precipitate. It should be noted that the supernatant can also be taken out by volatilizing it. The taken out precipitate can be dried, for example, by vacuum degassing, or natural drying, or a combination of vacuum degassing and natural drying. Natural drying can be implemented, for example, by placing it in the atmosphere at normal temperature and pressure. In this case, it can be placed for more than 20 hours, for example, about 30 hours.

[0058] Alternatively, the removed precipitate may be dispersed in an organic solvent. Purification (addition of alcohol and centrifugal separation) may be performed multiple times as needed. As the alcohol used in the purification, lower alcohols having 1 to 4 carbon atoms such as methanol, ethanol, and n-propanol may be used. When the precipitate is dispersed in an organic solvent, a halogen solvent such as chloroform, a hydrocarbon solvent such as toluene, cyclohexane, hexane, pentane, and octane may be used as the organic solvent.

[0059] Core-shell semiconductor nanoparticles

[0060] The semiconductor nanoparticles can be made into core-shell semiconductor nanoparticles having at least one of the semiconductor nanoparticles involved in the first embodiment and the semiconductor nanoparticles obtained by the manufacturing method involved in the second embodiment as a core, and having a shell having a band gap energy larger than that of the core and forming a heterojunction with the core. The semiconductor nanoparticles can show stronger band edge luminescence by having a core-shell structure.

[0061] The shell is preferably a semiconductor material consisting essentially of elements of Group 13 and Group 16. Examples of the Group 13 element include B, Al, Ga, In, and Tl, and examples of the Group 16 element include O, S, Se, Te, and Po.

[0062] In addition, the shell may be a semiconductor material substantially composed of Group 1 elements, Group 13 elements, and Group 16 elements. By including Group 1 elements in addition to Group 13 elements and Group 16 elements, there is a tendency to suppress defect luminescence. As Group 1 elements, Li, Na, K, Rb, and Cs can be cited, and Li is preferred in terms of an ionic radius close to that of Ag.

[0063] The band gap energy of the semiconductor constituting the core also depends on its composition. The semiconductors of the ternary system of Group 11-Group 13-Group 16 generally have a band gap energy of 1.0 eV or more and 3.5 eV or less, and in particular, the semiconductor composed of Ag-In-Ga-S has a band gap energy of 2.0 eV or more and 2.5 eV or less, so the shell can be selected according to the band gap energy of the semiconductor constituting the core and its composition is selected. Alternatively, when the composition of the shell is predetermined, the core can be designed in such a way that the band gap energy of the semiconductor constituting the core is smaller than the band gap energy of the shell.

[0064] Specifically, the shell may have a band gap energy of, for example, 2.0 eV or more and 5.0 eV or less, particularly 2.5 eV or more and 5.0 eV or less. In addition, the band gap energy of the shell may be greater than the band gap energy of the core, for example, 0.1 eV or more and 3.0 eV or less, particularly 0.3 eV or more and 3.0 eV or less, and more particularly 0.5 eV or more and 1.0 eV or less. If the difference between the band gap energy of the shell and the band gap energy of the core is small, sometimes the proportion of luminescence other than the band edge luminescence in the luminescence from the core becomes more, and the proportion of the band edge luminescence becomes smaller.

[0065] Furthermore, the band gap energy of the core and the shell is preferably selected in a type-I band alignment in which the band gap energy of the shell is given to sandwich the band gap energy of the core in the heterojunction between the core and the shell. By forming a type-I band alignment, the band edge luminescence from the core can be obtained more effectively. In the type-I arrangement, it is preferred to form a barrier of at least 0.1eV between the band gap of the core and the band gap of the shell, and in particular, a barrier of more than 0.2eV can be formed, and more particularly, a barrier of more than 0.3eV can be formed. The upper limit of the barrier is, for example, less than 1.8eV, and in particular, less than 1.1eV. If the barrier is small, sometimes the proportion of luminescence other than the band edge luminescence in the luminescence from the core becomes more, and the proportion of the band edge luminescence becomes smaller.

[0066] The shell may be a shell containing Ga as a Group 13 element and S as a Group 16 element. A semiconductor containing Ga and S tends to be a semiconductor having a larger band gap energy than a semiconductor of a Group 11-Group 13-Group 16 ternary system.

[0067] The shell can also be made into a shell whose semiconductor crystal system is fusible with the crystal system of the semiconductor of the core. In addition, its lattice constant can be the same as or close to the lattice constant of the semiconductor of the core. The shell containing semiconductors with fusible crystal systems and close lattice constants (here, semiconductors whose multiples of the lattice constant of the shell are close to the lattice constant of the core are also semiconductors with close lattice constants) sometimes covers the core well. For example, semiconductors of the ternary system of Group 11-Group 13-Group 16 are generally tetragonal systems, and as crystal systems that are fusible therewith, tetragonal systems and orthorhombic systems can be listed. In the case where the Ag-In-Ga-S semiconductor is a tetragonal system, it is preferred that: the lattice constant is The shell covering it is a tetragonal or cubic crystal system, and the lattice constant or a multiple thereof is close to the lattice constant of the Ag-In-Ga-S semiconductor. Alternatively, the shell may be amorphous.

[0068] Whether an amorphous shell is formed can be confirmed by observing the core-shell semiconductor nanoparticles with HAADF-STEM. According to HAADF-STEM, a shell having a regular structure like a crystalline material can be observed in the form of an image with a regular pattern, and a shell having no regular structure like an amorphous material cannot be observed in the form of an image with a regular pattern. Therefore, in the case where the shell is amorphous, the shell can be observed in the form of a portion that is clearly different from the core (having a crystal structure such as a tetragonal system as described above) observed as an image with a regular pattern.

[0069] In addition, when the core contains Ag-In-Ga-S and the shell contains GaS, since Ga is an element lighter than Ag and In, there is a tendency for the shell to be observed in the form of an image darker than the core in the image obtained using HAADF-STEM.

[0070] Whether an amorphous shell is formed can also be confirmed by observing the core-shell semiconductor nanoparticles with a high-resolution transmission electron microscope (HRTEM). In the image obtained by using HRTEM, the core portion can be observed in the form of a lattice image (an image with a regular pattern), the shell portion cannot be observed in the form of a lattice image, and the shell portion is observed in the form of a portion where a black-and-white contrast can be observed but no regular pattern is seen.

[0071] When the shell is a semiconductor including a combination of Ga and S as a combination of a Group 13 element and a Group 16 element, the combination of Ga and S may be in the form of gallium sulfide. Gallium sulfide constituting the shell may not be gallium sulfide (Ga2S3) of stoichiometric composition, which means that gallium sulfide may be referred to as GaS in this specification. x(x is an arbitrary number not limited to an integer, and is, for example, 0.8 or more and 1.5 or less).

[0072] The band gap energy of gallium sulfide is about 2.5eV or more and 2.6eV or less. For gallium sulfide with a tetragonal crystal system, its lattice constant is However, the crystal systems and the like described here are all reported values, and in actual core-shell semiconductor nanoparticles, the shell is not limited to satisfying these reported values. Gallium sulfide is preferably used as a semiconductor constituting the shell due to its larger band gap energy. When the shell is gallium sulfide, stronger band edge luminescence can be obtained.

[0073] In addition, when the shell is a semiconductor including a combination of Li, Ga and S as a combination of Group 1 elements, Group 13 elements and Group 16 elements, it can be in the form of, for example, lithium gallium sulfide. Lithium gallium sulfide may not be a stoichiometric composition (for example, LiGaS2), for example, the composition may be represented by LiGaSx (x is an arbitrary number not limited to an integer, for example, 1.1 to 2). In addition, it can be an amorphous form in which, for example, Li is solid-dissolved in gallium sulfide. The molar ratio of Li to Ga in the shell (Li / Ga) is, for example, 1 / 20 to 4 or 1 / 10 to 2.

[0074] The band gap energy of lithium gallium sulfide is relatively large, about 4eV, which can obtain stronger band edge luminescence. In addition, the size of the Li ion radius is equivalent to that of the Ag forming the core, so a structure similar to the shell and the core can be adopted, which is believed to compensate for the defects on the core surface and more effectively suppress defect luminescence.

[0075] The shell surface of core-shell semiconductor nanoparticles can be modified by surface modifiers. As the specific example of surface modifiers, except the nitrogen-containing compounds with hydrocarbon groups with more than 4 carbon atoms and less than 20 carbon atoms, sulfur-containing compounds with hydrocarbon groups with more than 4 carbon atoms and less than 20 carbon atoms, and oxygen-containing compounds with hydrocarbon groups with more than 4 carbon atoms and less than 20 carbon atoms, compounds (hereinafter also referred to as "specific modifiers") containing phosphorus with negative oxidation numbers can also be enumerated. By making the surface modifier of the shell include specific modifiers, the quantum yield in the band edge luminescence of the core-shell semiconductor nanoparticles is improved.

[0076] The specific modifier contains P having a negative oxidation number as a Group 15 element. The oxidation number of P is -1 due to the bonding of one hydrogen atom or an alkyl group to P, and is +1 due to the bonding of one oxygen atom to P by a single bond, and changes depending on the substitution state of P. For example, the oxidation number of P in trialkylphosphine and triarylphosphine is -3, and becomes -1 in trialkylphosphine oxide and triarylphosphine oxide.

[0077] The specific modifier may contain other elements of Group 15 in addition to P having a negative oxidation number. Examples of other elements of Group 15 include N, As, and Sb.

[0078] The specific modifier may be, for example, a phosphorus-containing compound having a hydrocarbon group having 4 to 20 carbon atoms. Examples of the hydrocarbon group having 4 to 20 carbon atoms include straight-chain or branched saturated aliphatic hydrocarbon groups such as n-butyl, isobutyl, n-pentyl, n-hexyl, octyl, ethylhexyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl; straight-chain or branched unsaturated aliphatic hydrocarbon groups such as oleyl; alicyclic hydrocarbon groups such as cyclopentyl and cyclohexyl; aromatic hydrocarbon groups such as phenyl and naphthyl; arylalkyl groups such as benzyl and naphthylmethyl, etc., among which saturated aliphatic hydrocarbon groups or unsaturated aliphatic hydrocarbon groups are preferred. When the specific modifier has multiple hydrocarbon groups, they may be the same or different.

[0079] Specific modifiers include, specifically, tributylphosphine, triisobutylphosphine, tripentylphosphine, trihexylphosphine, trioctylphosphine, tri(ethylhexyl)phosphine, tridecylphosphine, tridodecylphosphine, tritetradecylphosphine, trihexadecylphosphine, trioctadecylphosphine, triphenylphosphine, tributylphosphine oxide, triisobutylphosphine oxide, tripentylphosphine oxide, trihexylphosphine oxide, trioctylphosphine oxide, tri(ethylhexyl)phosphine oxide, tridecylphosphine oxide, tridodecylphosphine oxide, tritetradecylphosphine oxide, trihexadecylphosphine oxide, trioctadecylphosphine oxide, triphenylphosphine oxide, and the like. Preferably, it is at least one selected from them.

[0080] Method for producing core-shell semiconductor nanoparticles

[0081] The manufacturing method of core-shell semiconductor nanoparticles is a manufacturing method comprising the steps of preparing a dispersion liquid containing semiconductor nanoparticles and adding a semiconductor raw material to the dispersion liquid of semiconductor nanoparticles, and also comprising the step of forming a semiconductor layer on the surface of the semiconductor nanoparticles. When the semiconductor nanoparticles are covered with shells, the dispersion liquid formed by dispersing them in a suitable solvent is modulated, and the semiconductor layer to be the shell is formed in the dispersion liquid. In the liquid dispersed with semiconductor nanoparticles, no scattered light is generated, so the dispersion liquid is generally obtained in the form of a transparent (colored or colorless) dispersion liquid. The solvent for dispersing the semiconductor nanoparticles can be any organic solvent (especially an organic solvent with high polarity such as alcohol such as ethanol) in the same manner as when making semiconductor nanoparticles, and the organic solvent can be a surface modifier or a solution containing a surface modifier. For example, the organic solvent may be the surface modifier described in connection with the method for producing semiconductor nanoparticles, that is, at least one selected from nitrogen-containing compounds having a hydrocarbon group with a carbon number of 4 or more and 20 or less, or may be at least one selected from sulfur-containing compounds having a hydrocarbon group with a carbon number of 4 or more and 20 or less, or may be a combination of at least one selected from nitrogen-containing compounds having a hydrocarbon group with a carbon number of 4 or more and 20 or less and at least one selected from sulfur-containing compounds having a hydrocarbon group with a carbon number of 4 or more and 20 or less. As the nitrogen-containing compound, n-tetradecylamine, oleylamine, etc. are preferred from the perspective of being easy to obtain a particularly high-purity substance and making the boiling point exceed 290°C. As the sulfur-containing compound, dodecanethiol, etc. can be preferably cited. As a specific organic solvent, oleylamine, n-tetradecylamine, dodecanethiol, or a combination thereof can be cited.

[0082] The dispersion of semiconductor nanoparticles can be prepared according to the concentration of the particles in the dispersion, for example, 5.0×10 -7 mol / L and above 5.0×10 -5 mol / L or less, especially 1.0×10 -6 mol / L and above 1.0×10 -5 If the proportion of particles in the dispersion is too small, it is difficult to recover the product obtained by the coagulation and precipitation process using a poor solvent, and if it is too large, the proportion of fusion due to Ostwald ripening and collision of the materials constituting the core increases, and there is a tendency to make the particle size distribution wider.

[0083] Shell formation

[0084] The formation of the semiconductor layer to be the shell is performed, for example, by adding a compound containing a Group 13 element and a simple substance of a Group 16 element or a compound containing a Group 16 element to the above-mentioned dispersion.

[0085] The compound containing the Group 13 element is a compound that is a source of the Group 13 element, such as an organic salt, an inorganic salt, and an organometallic compound of the Group 13 element. Specifically, as the compound containing the Group 13 element, nitrates, acetates, sulfates, hydrochlorides, sulfonates, and acetylacetone complexes can be cited, and organic salts or organometallic compounds such as acetates are preferred. This is because organic salts and organometallic compounds have high solubility in organic solvents and are easy to react more uniformly.

[0086] A simple substance of a Group 16 element or a compound containing a Group 16 element is a compound that serves as a source of a Group 16 element. For example, when sulfur (S) which is a Group 16 element is used as a constituent element of the shell, a simple substance of sulfur such as high-purity sulfur can be used, or a thiol such as n-butyl mercaptan, isobutyl mercaptan, n-pentyl mercaptan, n-hexyl mercaptan, octyl mercaptan, decanethiol, dodecanethiol, hexadecanethiol, octadecanethiol, or the like, a disulfide such as dibenzyl sulfide, thiourea, or a sulfur-containing compound such as a thiocarbonyl compound can be used.

[0087] When oxygen (O) as a Group 16 element is used as a constituent element of the shell, alcohols, ethers, carboxylic acids, ketones, and N-oxide compounds can be used as a Group 16 element source. When selenium (Se) as a Group 16 element is used as a constituent element of the shell, selenium alone or compounds such as phosphine selenide oxide, organic selenium compounds (dibenzyl diselenide or diphenyl diselenide) or hydrides can be used as a Group 16 element source. When tellurium (Te) as a Group 16 element is used as a constituent element of the shell, tellurium alone, phosphine telluride oxide or hydride can be used as a Group 16 element source.

[0088] The method of adding the 13th group element source and the 16th group element source to the dispersion is not particularly limited. For example, the 13th group element source and the 16th group element source can be prepared to disperse or dissolve in a mixed solution of an organic solvent, and the mixed solution can be added in small amounts and multiple times, for example, by dropping the mixed solution into the dispersion. In this case, the mixed solution can be added at a speed of more than 0.1 mL / hour and less than 10 mL / hour, especially more than 1 mL / hour and less than 5 mL / hour. In addition, the mixed solution can be added to the heated dispersion. Specifically, for example, a shell layer can be formed by the following method: the dispersion is heated to a peak temperature of more than 200°C and less than 310°C, and after reaching the peak temperature, the mixed solution is added in small amounts and multiple times while maintaining the peak temperature, and then cooled (slow injection method). The peak temperature can be maintained as needed after the addition of the mixed solution is completed.

[0089] If the peak temperature is above the above-mentioned temperature, then based on the surface modifier modified semiconductor nanoparticles fully break away from or for shell generation of chemical reaction fully carried out and other reasons, and there is a tendency to fully carry out the formation of the layer (shell) of semiconductor. If the peak temperature is below the above-mentioned temperature, then suppress the semiconductor nanoparticles to produce deterioration, there is a tendency to obtain good band edge luminescence. The time of keeping the peak temperature can be from the addition of the starting mixed solution to a total of more than 1 minute and less than 300 minutes, especially more than 10 minutes and less than 120 minutes. The holding time of the peak temperature is selected according to its relationship with the peak temperature, if the holding time is further extended when the peak temperature is lower and the holding time is further shortened when the peak temperature is higher, then it is easy to form a good shell. The heating rate and the cooling rate are not particularly limited, and cooling can be implemented by stopping the heating based on the heating source (such as electric heater) after keeping the prescribed time at the peak temperature, for example.

[0090] Alternatively, the 13th group element source and the 16th group element source can be directly added to the dispersion in full amount. Afterwards, the dispersion added with the 13th group element source and the 16th group element source can be heated to form a semiconductor layer as a shell on the surface of the semiconductor nanoparticle (heating up method). Specifically, the dispersion added with the 13th group element source and the 16th group element source can be heated by, for example, gradually heating the peak temperature to be above 200°C and below 310°C, and then keeping it at the peak temperature for more than 1 minute and less than 300 minutes, and then gradually cooling it down. The heating rate can be, for example, above 1°C / minute and below 50°C / minute, and the cooling rate can be, for example, above 1°C / minute and below 100°C / minute. Alternatively, heating can be performed in a manner that the prescribed peak temperature is reached without particularly controlling the heating rate. In addition, cooling can also be performed by stopping the heating based on the heating source and performing natural cooling without implementing cooling at a certain speed. The advantage of the peak temperature being the above range is as shown in the description of the method for adding the above-mentioned mixed solution (slow injection method).

[0091] According to the temperature ramp method, there is a tendency that core-shell type semiconductor nanoparticles having stronger band edge emission can be obtained compared to the case where the shell is formed by the slow injection method.

[0092] Even when adding a source of a Group 13 element and a source of a Group 16 element by any method, the input ratio of the two can be determined according to the stoichiometric composition ratio of the compound semiconductor containing the Group 13 element and the Group 16 element, or it does not have to be a stoichiometric composition ratio. In the case where the input ratio is not a stoichiometric composition ratio, the raw material can be input in excess of the target shell generation amount, for example, the Group 16 element source can be made less than the stoichiometric composition ratio, for example, the input ratio can be made 1:1 (Group 13: Group 16). For example, when an In source is used as a Group 13 element source and an S source is used as a Group 16 element source, the input ratio is preferably 1:1.5 (In:S) to 1:1 corresponding to the composition formula of In2S3. Similarly, when a Ga source is used as a Group 13 element source and an S source is used as a Group 16 element source, the input ratio is preferably 1:1.5 (Ga:S) to 1:1 corresponding to the composition formula of Ga2S3.

[0093] In addition, in order to form a shell of desired thickness for the semiconductor nanoparticles present in the dispersion, the input amount is selected in consideration of the amount of semiconductor nanoparticles contained in the dispersion. For example, the input amount of the source of the 13th group element and the source of the 16th group element can be determined in such a way that 1 μmol or more and 10 mmol or less, especially 5 μmol or more and 1 mmol or less of a compound semiconductor having a stoichiometric composition containing the 13th group element and the 16th group element are generated relative to 10 nmol of the substance as particles of the semiconductor nanoparticles. However, the amount of the substance as particles is the molar amount when one particle is regarded as a giant molecule, which is different from the number of nanoparticles contained in the dispersion divided by the Avogadro constant (N). A =6.022×10 23 ) are equal.

[0094] In the method for producing core-shell semiconductor nanoparticles, it is preferred to use indium acetate or gallium acetylacetonate as a source of a Group 13 element, sulfur, thiourea or dibenzyl disulfide as a source of a Group 16 element, and a mixed solution of oleylamine and dodecanethiol as a dispersion solution to form a shell containing indium sulfide or gallium sulfide.

[0095] In addition, if a mixed solution of oleylamine and dodecanethiol is used as a dispersion liquid in the temperature rise method, core-shell semiconductor nanoparticles are obtained that give a luminescence spectrum in which the intensity of a broad peak of defect luminescence is sufficiently smaller than the intensity of a peak of band edge luminescence. The above-mentioned significant tendency is also confirmed when a gallium source is used as a Group 13 element source.

[0096] In this way, a shell is formed to form a core-shell semiconductor nanoparticle. The obtained core-shell semiconductor nanoparticle can be separated from the solvent, and can also be further purified and dried as needed. The method of separation, purification and drying is shown in the description associated with the semiconductor nanoparticle before, so its detailed description is omitted here.

[0097] In addition, when the semiconductor that becomes the shell is substantially composed of Group 1 elements, Group 13 elements, and Group 16 elements, the shell can also be formed in the same manner as described above. That is, a compound containing a Group 1 element, a compound containing a Group 13 element, and a simple substance of a Group 16 element or a compound containing a Group 16 element can be added to a dispersion of semiconductor nanoparticles that become the core to form the shell.

[0098] Compounds containing Group 1 elements are, for example, organic salts, inorganic salts, and organometallic compounds of Group 1 elements. Specifically, compounds containing Group 1 elements include nitrates, acetates, sulfates, hydrochlorides, sulfonates, and acetylacetone complexes, preferably organic salts or organometallic compounds such as acetates. This is because organic salts and organometallic compounds have high solubility in organic solvents and are more likely to react more uniformly.

[0099] When the shell surface of the core-shell semiconductor nanoparticle is modified with a specific modifier, the core-shell semiconductor nanoparticle obtained above can be provided in the modification process. In the modification process, the core-shell semiconductor nanoparticle is contacted with a specific modifier containing phosphorus (P) having a negative oxidation number, and the shell surface of the core-shell particle is modified. Thus, semiconductor nanoparticles showing band edge luminescence are manufactured with a more excellent quantum yield.

[0100] The contact between the core-shell semiconductor nanoparticles and the specific modifier can be carried out, for example, by mixing a dispersion of the core-shell semiconductor nanoparticles and the specific modifier. Alternatively, the core-shell particles can be mixed with a liquid specific modifier. For the specific modifier, a solution thereof can be used. The dispersion of the core-shell semiconductor nanoparticles is obtained by mixing the core-shell semiconductor nanoparticles with a suitable organic solvent. Examples of the organic solvent used in the dispersion include: halogen solvents such as chloroform; aromatic hydrocarbon solvents such as toluene; aliphatic hydrocarbon solvents such as cyclohexane, hexane, pentane, and octane. The concentration of the amount of the core-shell semiconductor nanoparticles in the dispersion is, for example, 1×10 -7 mol / L and above 1×10 -3 mol / L or less, preferably 1×10 -6 mol / L and above 1×10 -4 The amount of the substance mentioned here is as described in the shell formation.

[0101] The amount of the specific modifier used relative to the core-shell type semiconductor nanoparticles is, for example, 1 to 50,000 times in molar ratio. In addition, when the concentration of the core-shell type semiconductor nanoparticles in the dispersion is 1.0×10 -7 mol / L and above 1.0×10 -3 In the case of a dispersion of core-shell type semiconductor nanoparticles at a concentration of mol / L or less, the dispersion and the specific modifier may be mixed at a volume ratio of 1:1000 to 1000:1.

[0102] The temperature when the core-shell semiconductor nanoparticles are in contact with the specific modifier is, for example, above -100°C and below 100°C or above -30°C and below 75°C. The contact time can be appropriately selected according to the amount of the specific modifier used, the concentration of the dispersion, etc. The contact time is, for example, more than 1 minute, preferably more than 1 hour, and less than 100 hours, preferably less than 48 hours. The atmosphere during contact is, for example, an inert gas atmosphere such as nitrogen or a rare gas.

[0103] Light-emitting devices

[0104] The light-emitting device involved in the third embodiment includes a light conversion component containing semiconductor nanoparticles and / or core-shell semiconductor nanoparticles and a semiconductor light-emitting element. According to the light-emitting device, for example, the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles absorb a part of the light emitted from the semiconductor light-emitting element and emit light with a longer wavelength. In addition, the light from the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles and the remainder of the light emitted from the semiconductor light-emitting element can be mixed, and the mixed light can be used as the light emission of the light-emitting device.

[0105] Specifically, if a component emitting a bluish-purple light or a blue light having a peak wavelength of about 400 nm or more and about 490 nm or less is used as a semiconductor light emitting element, and a semiconductor nanoparticle that absorbs blue light and emits yellow light is used as a semiconductor nanoparticle and / or a core-shell type semiconductor nanoparticle, a light emitting device emitting white light can be obtained. Alternatively, a semiconductor nanoparticle that absorbs blue light and emits green light and a semiconductor nanoparticle that absorbs blue light and emits red light can also be used as semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles to obtain a white light emitting device.

[0106] Alternatively, a white light emitting device can also be obtained by using a semiconductor light emitting element that emits ultraviolet light with a peak wavelength of less than 400nm and using three kinds of semiconductor nanoparticles and / or core-shell semiconductor nanoparticles that absorb ultraviolet light and emit blue light, green light, and red light respectively. In this case, it is desirable that all the light from the light emitting element is absorbed by the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles and converted in a manner that does not allow the ultraviolet light emitted from the light emitting element to leak to the outside.

[0107] The semiconductor nanoparticles and / or core-shell semiconductor nanoparticles of the present embodiment can be used in combination with other semiconductor quantum dots, or can be used in combination with other phosphors that are not semiconductor quantum dots (such as organic phosphors or inorganic phosphors). Other semiconductor quantum dots are, for example, binary semiconductor quantum dots described in the background technology column. As phosphors that are not semiconductor quantum dots, garnet phosphors such as aluminum garnet can be used. As garnet phosphors, yttrium-aluminum-garnet phosphors activated by cerium and lutetium-aluminum-garnet phosphors activated by cerium can be listed. In addition, it is also possible to use: nitrogen-containing calcium aluminosilicate phosphors activated by europium and / or chromium, silicate phosphors activated by europium, β-SiAlON phosphors, nitride phosphors such as CASN or SCASN; rare earth nitride phosphors such as LnSi3N11 or LnSiAlON; BaSi2O2N2:Eu or Ba3Si6O 12 Nitrogen oxide phosphors such as N2:Eu series; sulfide phosphors such as CaS series, SrGa2S4 series, SrAl2O4 series, and ZnS series; chlorosilicate phosphors; SrLiAl3N4:Eu phosphor; SrMg3SiN4:Eu phosphor; K2SiF6:Mn phosphor which is a fluoride complex phosphor activated by manganese, etc.

[0108] In the light-emitting device, the light conversion member containing semiconductor nanoparticles and / or core-shell semiconductor nanoparticles may be, for example, a sheet or plate-like member, or may be a member having a three-dimensional shape. An example of a member having a three-dimensional shape is a sealing member formed by filling a resin in a concave portion formed in a package body in order to seal the light-emitting element when a semiconductor light-emitting element is arranged on the bottom surface of the concave portion formed in the package body in a surface-mounted light-emitting diode.

[0109] Alternatively, another example of the light conversion member is: when a semiconductor light emitting element is arranged on a flat substrate, a resin member is formed in a manner to surround the upper surface and side surfaces of the semiconductor light emitting element with a substantially uniform thickness. Alternatively, another example of the light conversion member is: when a resin member containing a reflective material is filled around the semiconductor light emitting element so that the upper end of the resin member and the semiconductor light emitting element form the same plane, a resin member is formed in a flat plate shape with a predetermined thickness on the upper part of the semiconductor light emitting element and the resin member containing a reflective material.

[0110] The light conversion component can be in contact with the semiconductor light emitting element, or can be set separately from the semiconductor light emitting element. Specifically, the light conversion component can be a granular component, a sheet component, a plate-like component or a rod-like component that is separated and configured from the semiconductor light emitting element, or can be a component that is set in contact with the semiconductor light emitting element, such as a sealing component, a coating component (a component that covers the light emitting element and is set separately from the mold component) or a mold component (for example, a component that includes a lens shape). In addition, when two or more semiconductor nanoparticles of the present invention or core-shell semiconductor nanoparticles that show light emission of different wavelengths are used in the light emitting device, the above-mentioned two or more semiconductor nanoparticles of the present invention and / or core-shell semiconductor nanoparticles can be mixed in one light conversion component, or two or more light conversion components that only contain one quantum dot can be used in combination. In this case, the two or more light conversion components can form a stacked structure, or can be configured in a dot-like or strip-like pattern on a plane.

[0111] As the semiconductor light emitting element, an LED chip can be cited. The LED chip can be a chip having a semiconductor layer containing one or more substances selected from GaN, GaAs, InGaN, AlInGaP, GaP, SiC, and ZnO. A semiconductor light emitting element that emits bluish-violet light, blue light, or ultraviolet light preferably has a general formula In X Al Y Ga 1-X-Y An element in which a GaN-based compound represented by N (0≤X, 0≤Y, X+Y<1) is used as a semiconductor layer.

[0112] The light-emitting device is preferably assembled into a liquid crystal display device as a light source. The band edge luminescence of the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles based on the present invention has a short luminescence lifetime, so the light-emitting device using them is suitable as a light source for a liquid crystal display device that requires a faster response speed. In addition, the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles of the present invention can show a luminescence peak with a small half-value width as band edge luminescence. Therefore,

[0113] - In a light-emitting device, a blue semiconductor light-emitting element is used to obtain blue light with a peak wavelength in the range of 420 nm to 490 nm, and the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles of the present invention are used to obtain green light with a peak wavelength in the range of 510 nm to 550 nm, preferably in the range of 530 nm to 540 nm, and red light with a peak wavelength in the range of 600 nm to 680 nm, preferably in the range of 630 nm to 650 nm; or

[0114] - In a light-emitting device, ultraviolet light with a peak wavelength of 400 nm or less is obtained by using a semiconductor light-emitting element, and blue light with a peak wavelength in the range of 430 nm to 470 nm, preferably 440 nm to 460 nm, green light with a peak wavelength in the range of 510 nm to 550 nm, preferably 530 nm to 540 nm, and red light with a peak wavelength in the range of 600 nm to 680 nm, preferably 630 nm to 650 nm, is obtained by using the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles of the present invention;

[0115] In summary, a liquid crystal display device with good color reproducibility can be obtained without using a dark color filter. The light emitting device of this embodiment is used as, for example, a direct type backlight or an edge type backlight.

[0116] Alternatively, a sheet, plate-like member or rod made of resin or glass or the like containing the semiconductor nanoparticles and / or core-shell semiconductor nanoparticles of the present invention may be incorporated into a liquid crystal display device as a light conversion member independent of a light-emitting device.

[0117] Example

[0118] Hereinafter, the present invention will be described in more detail using examples; however, the present invention is not limited to these examples.

[0119] (Example 1)

[0120] 0.1402 mmol of silver acetate (AgOAc), 0.1875 mmol of indium acetate (In(OAc)3), 0.047 mmol of gallium acetate (Ga(OAc)3), and 0.3744 mmol of thiourea as a sulfur source were added and dispersed in a 0.05 cm 3 1-dodecanethiol and 2.95cm 3The dispersion was added to a test tube together with a stirrer, and after nitrogen substitution, the contents of the test tube were stirred under a nitrogen atmosphere while being heated at 150°C for 10 minutes as the first stage of heating treatment and at 250°C for 10 minutes as the second stage of heating treatment. After the heating treatment, the obtained suspension was naturally cooled, centrifuged (radius 146 mm, 4000 rpm, 5 minutes), and the dispersion was taken out as the supernatant. Methanol was added thereto until precipitation of semiconductor nanoparticles was produced, and centrifuged (radius 146 mm, 4000 rpm, 5 minutes) was performed to precipitate the semiconductor nanoparticles. The precipitate was taken out and dispersed in chloroform to obtain a semiconductor nanoparticle dispersion. The input composition of the raw materials is shown in Table 1.

[0121] (Examples 2 and 3)

[0122] Except having changed the charge composition of raw materials as shown in Table 1, it carried out similarly to Example 1, and obtained the semiconductor nanoparticle dispersion liquid.

[0123] [Table 1]

[0124]

[0125] (Example 4)

[0126] 0.125 mmol of silver acetate (AgOAc), 0.0375 mmol of indium acetylacetonate (In(CH3COCHCOCH3)3; In(AcAc)3), 0.0875 mmol of gallium acetylacetonate (Ga(CH3COCHCOCH3)3; Ga(AcAc)3) and 0.25 mmol of sulfur as a sulfur source were added and dispersed in 0.25 cm 3 1-dodecanethiol and 2.75cm 3 The dispersion was added to a test tube together with a stirrer, and after nitrogen substitution, the contents in the test tube were heated at 300°C for 10 minutes while stirring in a nitrogen atmosphere. After the heat treatment, post-treatment was performed in the same manner as in Example 1 to obtain a semiconductor nanoparticle dispersion. The input composition of the raw materials is shown in Table 2.

[0127] (Examples 5 to 8)

[0128] Except for changing the raw material input composition and heat treatment conditions as shown in Table 2, the same procedure as in Example 4 was carried out to obtain a semiconductor nanoparticle dispersion.

[0129] (Example 9)

[0130] Fabrication of semiconductor nanoparticle cores

[0131] The raw material input composition and heat treatment conditions were set as shown in Table 2, and the heat treatment was carried out in the same manner as above to obtain a semiconductor nanoparticle core dispersion.

[0132] (Examples 10 and 11)

[0133] Preparation of core-shell semiconductor nanoparticles

[0134] In the dispersion of semiconductor nanoparticle cores obtained in Example 9, 1.0×10 -5 mmol, and the solvent was evaporated in a test tube. -5 mol of Ga(AcAc)3 (19.3mg) and thiourea (2.75mg) were dispersed in a mixed solvent of 2.75mL of oleylamine and 0.25mL of dodecanethiol to form a dispersion, which was stirred at 300°C for 120 minutes under a nitrogen atmosphere. It was taken out from the heating source, cooled naturally to room temperature, and centrifuged (radius 150mm, 4000rpm, 5 minutes) to separate the supernatant and the precipitate. After that, methanol was added to each, and after obtaining the precipitate of core-shell semiconductor nanoparticles, the solid component was recovered by centrifugation (radius 150mm, 4000rpm, 5 minutes). Ethanol was added again, and centrifugation was performed in the same manner, and each was dispersed in chloroform and various measurements were performed. In addition, the average particle size of the particles covered by the shell was measured, and the core-shell particles obtained by the precipitation were 4.3nm, and the particles obtained by the supernatant were 3.5nm, and the thickness of the shell obtained by the difference from the average particle size of the semiconductor nanoparticle core was about 0.75nm and 0.35nm respectively on average. Hereinafter, the core-shell semiconductor nanoparticle dispersion obtained from the supernatant portion is set as Example 10, and the core-shell semiconductor nanoparticle dispersion obtained from the precipitation portion is set as Example 11.

[0135] [Table 2]

[0136]

[0137] (Comparative Example 1)

[0138] Silver acetate (AgOAc) and indium acetate (In(OAc)3) were weighed so that Ag / Ag+In were 0.3 (Comparative Example 1), 0.4 (Comparative Example 3), and 0.5 (Comparative Example 2), respectively, and the total amount of the two metal salts was 0.25 mmol. Silver acetate (AgOAc), indium acetate (In(OAc)3), and 0.25 mmol of thiourea were added and dispersed in a 0.10 cm 3 Oleylamine and 2.90cm 3The dispersion was added to a test tube together with a stirrer, and after nitrogen substitution, the contents in the test tube were heated at 150°C for 10 minutes under a nitrogen atmosphere while stirring as the first stage of heat treatment, and then heated at 250°C for 10 minutes as the second stage of heat treatment. After the heat treatment, the obtained suspension was naturally cooled and centrifuged (radius 146 mm, 4000 rpm, 5 minutes) to precipitate the semiconductor nanoparticles.

[0139] Regarding Comparative Example 1, the obtained precipitate was washed with methanol, chloroform was added to the precipitate, centrifuged (radius 146 mm, 4000 rpm, 15 minutes), and the supernatant was recovered to obtain a semiconductor nanoparticle dispersion. Regarding Comparative Examples 3 and 2, methanol was added to the dispersion as the supernatant until the precipitation of nanoparticles was generated, and centrifuged (radius 146 mm, 4000 rpm, 5 minutes) was performed to precipitate semiconductor nanoparticles. The precipitate was taken out and dispersed in chloroform to obtain semiconductor nanoparticle dispersions.

[0140] (Composition Analysis)

[0141] For the obtained semiconductor nanoparticles, a fluorescent X-ray analyzer was used to determine the ratio of each atom when the total number of atoms of Ag, In, Ga, and S contained in the semiconductor nanoparticles was set to 100, and the Ga ratio calculated as Ga / (Ga+In), the Ag ratio calculated as Ag / (Ag+In+Ga), and the S ratio calculated as S / (Ag+In+Ga) were calculated. The results are shown in Table 3.

[0142] (Average particle size)

[0143] The shape of the obtained semiconductor nanoparticles was observed, and the average particle size was measured. The shape of the obtained particles was spherical or polygonal. The average particle size is shown in Table 3.

[0144] (Luminescence characteristics)

[0145] The absorption and emission spectra of the obtained semiconductor nanoparticles were measured. Regarding the absorption spectrum, a diode array spectrophotometer (manufactured by Agilent Technologies, trade name Agilent 8453A) was used to measure the wavelength at 190 nm or more and 1100 nm or less. Regarding the emission spectrum, a multi-channel spectrometer (manufactured by Hamamatsu Photonics, trade name PMA11) was used to measure the excitation wavelength at 365 nm. The emission spectra of Examples 3, 4, 6 and Comparative Example 3 are shown in Figure 1 The absorption spectrum is shown in Figure 2 The luminescence spectra of Examples 10 and 11 are shown in Figure 4The absorption spectrum is shown in Figure 5 The peak wavelength (band edge emission) and half-value width of the steep emission peak observed in each emission spectrum are shown in Table 3. In addition, the ratio of the band edge emission intensity to the emission peak intensity of the DAP (donor-acceptor pair) transition (Bandedge / DAP) was determined.

[0146] (X-ray diffraction pattern)

[0147] The X-ray diffraction (XRD) pattern of the semiconductor nanoparticles obtained in Example 4 was measured and compared with that of tetragonal (chalcopyrite-type) AgInS2 and orthorhombic AgInS2. The measured XRD pattern is shown in Figure 3 From the XRD spectrum, it can be seen that the crystal structure of the semiconductor nanoparticles of Example 4 is substantially the same as that of tetragonal AgInS2. The XRD spectrum was measured using a powder X-ray diffraction device (trade name SmartLab) manufactured by Rigaku Corporation.

[0148] [Table 3]

[0149]

[0150] It can be seen from Table 3 that the semiconductor nanoparticles of the present embodiment exhibit band-edge luminescence having a luminescence peak wavelength shorter than that of Comparative Example 3. In addition, it can be seen from the results of Examples 10 and 11 that even if the manufacturing method of the semiconductor nanoparticles is the same, when the average particle size of the obtained semiconductor nanoparticles is small, the luminescence wavelength of the band-edge luminescence will be shortened.

[0151] (Example 12)

[0152] 0.0833 mmol of silver acetate (AgOAc), 0.050 mmol of In(AcAc)3, 0.075 mmol of Ga(AcAc)3, and 0.229 mmol of sulfur as a sulfur source were added and dispersed in a 0.25 cm 3 1-dodecanethiol and 2.75cm 3 The dispersion is added to a mixture of oleylamine and 1,2-diol. The dispersion is added to a test tube together with a stirrer, and after nitrogen substitution, the contents of the test tube are heated at 300°C for 10 minutes while stirring in a nitrogen atmosphere. After the heat treatment, the resulting suspension is naturally cooled, centrifuged (radius 146 mm, 4000 rpm, 5 minutes), and the dispersion is taken out as the supernatant. Methanol is added thereto until precipitation of semiconductor nanoparticles occurs, and centrifuged (radius 146 mm, 4000 rpm, 5 minutes) is performed to precipitate the semiconductor nanoparticles. The precipitate is taken out and dispersed in chloroform to obtain a semiconductor nanoparticle dispersion.

[0153] Preparation of core-shell semiconductor nanoparticles

[0154] In the dispersion of the semiconductor nanoparticle cores obtained above, 1.0×10 -5 mmol, and the solvent was evaporated in a test tube. -5 mol of Ga(AcAc)3, 5.33×10 -5 mol of thiourea, 2.67×10 -5 mol of lithium acetate and 3.0mL of oleylamine and disperse them to form a dispersion. The molar ratio of Li to Ga in the dispersion (Li / Ga) is 1 / 2. Then, the dispersion is stirred at 300°C for 15 minutes under a nitrogen atmosphere. It is taken out from the heat source, naturally cooled to room temperature, and centrifuged (radius 150mm, 4000rpm, 5 minutes) to separate it into a supernatant and a precipitate. After that, methanol is added to the supernatant to obtain a precipitate of core-shell semiconductor nanoparticles, and then the solid component is recovered by centrifugation (radius 150mm, 4000rpm, 5 minutes). Ethanol is added again, and centrifugation is performed in the same manner, and each is dispersed in chloroform and various measurements are performed. In addition, the average particle size of the particles covered by the shell was measured, and the result was 4.7nm, and the thickness of the shell obtained by the difference from the average particle size of the semiconductor nanoparticle core was about 0.75nm on average.

[0155] The obtained core-shell semiconductor nanoparticles were subjected to composition analysis and luminescence spectrum measurement in the same manner as above. The evaluation results are shown in Table 4, and the luminescence spectrum is shown in Figure 6 middle.

[0156] (Examples 13 to 16)

[0157] The amount of Ga(AcAc)3 and thiourea was fixed at 5.33×10 -5 The core-shell type semiconductor nanoparticles were prepared in the same manner as in Example 12 except that the amount of lithium acetate added was changed so as to set the molar ratio of Li to Ga (Li / Ga) in the dispersion as shown in the following table. The evaluation results are shown in Table 4, and the emission spectra are shown in Figure 6 middle.

[0158] (Examples 17-18)

[0159] The amount of lithium acetate and thiourea was fixed at 5.33 × 10 -5mol, and the amount of Ga(AcAc)3 added was changed in such a way that the molar ratio of Li to Ga (Li / Ga) in the dispersion was set as shown in the following table. Core-shell type semiconductor nanoparticles were prepared in the same manner as in Example 12. The evaluation results are shown in Table 4, and the emission spectra are shown in Figure 7 middle.

[0160] [Table 4]

[0161]

[0162] By including Li as a Group 1 element in the shell, DAP emission as defect emission is reduced and the intensity of band edge emission is increased. When Li is increased compared to Ga, the emission wavelength of the band edge emission shifts to a shorter wavelength.

[0163] (Example 19)

[0164] To the dispersion of core-shell semiconductor nanoparticles obtained in Example 12, approximately the same volume of trioctylphosphine (TOP) was added under a nitrogen atmosphere, and after shaking and mixing at room temperature for 10 minutes, the mixture was allowed to stand at room temperature for 20 hours under light shielding to obtain a dispersion of core-shell semiconductor nanoparticles modified with TOP.

[0165] The TOP modified core-shell semiconductor nanoparticles were subjected to the same luminescence spectrum measurement as above and the internal quantum yield measurement. The internal quantum yield of the core-shell semiconductor nanoparticles was 13.5%, while the internal quantum yield of the TOP modified core-shell semiconductor nanoparticles was 31.4%. The luminescence spectrum is shown in Figure 8 middle.

[0166] The entire disclosure of Japanese Patent Application No. 2017-037477 (filing date: February 28, 2017) and Japanese Patent Application No. 2018-025251 (filing date: February 15, 2018) is incorporated into this specification by reference. All documents, patent applications, and technical standards described in this specification are incorporated into this specification by reference to the same extent as if each document, patent application, and technical standard was specifically and individually described as being cited as a reference.

Claims

1. A nanoparticle, which is composed of a semiconductor nanoparticle and a semiconductor layer formed on the surface of the semiconductor nanoparticle, The semiconductor nanoparticles include Ag, In, Ga and S, The ratio of the number of Ga atoms to the total number of In and Ga atoms is 0.2 or more and 0.9 or less, The ratio of the number of Ag atoms to the total number of Ag, In, and Ga atoms is 0.05 or more and 0.55 or less, The ratio of the number of S atoms to the total number of Ag, In and Ga atoms is 0.6 or more and 1.6 or less, The semiconductor layer includes a semiconductor material with a larger band gap energy than that of the semiconductor nanoparticles, and the band gap energy of the semiconductor layer is greater than or equal to 2.5 eV and less than or equal to 5.0 eV. The semiconductor material comprises a Group 13 element and a Group 16 element, The Group 13 element is selected from B, Al, Ga, In, Tl, The Group 16 element is selected from O, S, Se, Te, The half-value width of the luminescence peak of the nanoparticles is less than 70 nm.

2. The nanoparticle according to claim 1, wherein The emission peak wavelength is in the range of 500 nm to less than 590 nm.

3. The nanoparticle according to claim 1, wherein The ratio of the number of Ag atoms to the total number of Ag, In, and Ga atoms is 0.3 or more and 0.55 or less, The ratio of the number of Ga atoms to the total number of In and Ga atoms is 0.5 or more and 0.9 or less.

4. The nanoparticle according to claim 1, wherein The ratio of the number of Ag atoms to the total number of Ag, In, and Ga atoms is 0.05 or more and 0.27 or less, The ratio of the number of Ga atoms to the total number of In and Ga atoms is 0.25 or more and 0.75 or less.

5. The nanoparticle according to claim 1, wherein The average particle size of the semiconductor nanoparticles is less than 10 nm.

6. The nanoparticle according to claim 1, wherein The semiconductor material contains at least Ga as the Group 13 element.

7. The nanoparticle according to claim 1, wherein The semiconductor material contains at least S as the Group 16 element.

8. A light conversion component, comprising: The nanoparticle according to any one of claims 1 to 7.

9. The light conversion component according to claim 8, wherein: It also contains at least one selected from semiconductor nanoparticles other than the nanoparticles, organic phosphors, and inorganic phosphors.

10. The light conversion component according to claim 8 or 9, wherein: The light conversion member is a sheet or plate-shaped member.

11. A light emitting device comprising: The light conversion component according to any one of claims 8 to 10; A semiconductor light emitting element having a peak emission wavelength of 400nm to 490nm.

12. A liquid crystal display device comprising the light emitting device according to claim 11.

Citation Information

Patent Citations

  • Light emitting diode unit and display device including the same

    JP2010177656A

  • Laminate for white LED, and white LED

    JP2012212862A

  • Tellurium compound nanoparticle and composite nanoparticle and manufacturing method therefor

    JP2017014476A

  • Semiconductor nanoparticle and manufacturing method therefor

    JP2017025201A

  • Waiting time estimation system and waiting time estimation method

    JP2017037477A